bahasa indonesia bahasa inggris - Putri Puspita; Sukrin Sukrin; Ade S. Anhar; Ahmad (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
This study aims to (1) analyze the implementation of the Read Aloud and Singing methods in learning, (2) examine children's responses and involvement during learning activities, (3) Impact on the development of anti-bullying characters in early childhood. The research uses a qualitative approach with the type of case study conducted at RA Al-Ikhlas, Bima City with subjects of group B children aged 4–6 years as well as informants of school principals and classroom teachers. The data collection technique was carried out through participatory observation, in-depth interviews, and documentation, while the data analysis used an interactive model by Miles and Huberman with the stages of data reduction, data presentation, and conclusion drawn, as well as validity test through triangulation. The results of the study show that the integration of Read Aloud and Singing methods in learning is able to support the development of anti-bullying characters, which is shown through increased empathy, social concern, mutual respect, cooperation, and a decrease in aggressive behavior in children. The implementation of learning is carried out systematically through the stages of planning, implementation, evaluation, and reflection, although there are still challenges in the form of differences in the level of understanding of children in receiving moral messages. The implication is that the integration of literacy and musical activities can be an effective learning strategy in instilling character values. Teachers are recommended to systematically integrate storytelling and singing activities into learning themes that promote empathy, tolerance, and mutual respect as an effort to strengthen anti-bullying character values in early childhood.